Impact of Arterial Stiffness on All-Cause Mortality in Patients Hospitalized With COVID-19 in Spain. Issue 3 (30th December 2020) - Rodilla, Enrique; López-Carmona, Maria Dolores; Cortes, Xavi; Cobos-Palacios, Lidia; Canales, Sergio; Sáez, Maria Carmen; Campos Escudero, Samara; Rubio-Rivas, Manuel; Díez Manglano, Jesus; Freire Castro, Santiago J.; Vázquez Piqueras, Nuria; Mateo Sanchis, Elisabeth; et al.
Abstract : Older age and cardiovascular comorbidities are well-known risk factors for all-cause mortality in patients with coronavirus disease 2019 (COVID-19). Hypertension and age are the 2 principal determinants of arterial stiffness (AS). This study aimed to estimate AS in patients with COVID-19 requiring hospitalization and analyze its association with all-cause in-hospital mortality. This observational, retrospective, multicenter cohort study analyzed 12 170 patients admitted to 150 Spanish centers included in the SEMI-COVID-19 Network. We compared AS, defined as pulse pressure ≥60 mm Hg, and clinical characteristics between survivors and nonsurvivors. Mean age was 67.5 (±16.1) years and 42.5% were women. Overall, 2606 (21.4%) subjects died. Admission systolic blood pressure (BP) <120 and ≥140 mm Hg was a predictor of higher all-cause mortality (23.5% and 22.8%, respectively, P <0.001), compared with systolic BP between 120 and 140 mm Hg (18.6%). The 4379 patients with AS (36.0%) were older and had higher systolic and lower diastolic BP. Multivariate analysis showed that AS and systolic BP <120 mm Hg significantly and independently predicted all-cause in-hospital mortality (adjusted odds ratio [ORadj]: 1.27, P =0.0001; ORadj: 1.48, P =0.0001, respectively) after adjusting for sex (males, ORadj: 1.6, P =0.0001), age tertiles (second and third tertiles, ORadj: 2.0 and 4.7, P =0.0001), Charlson Comorbidity Index (second and third tertiles, ORadj: 4.8 and 8.6, P =0.0001), heart failure, and previous and in-hospital antihypertensive treatment. Our data show that AS and admission systolic BP <120 mm Hg had independent prognostic value for all-cause mortality in patients with COVID-19 requiring hospitalization.